Academic Libraries and Copyright: Do Librarians Really Have the Required Knowledge? - Fernandez-Molina, Juan-Carlos; Moraes, Joao Batista E. [UNESP]; Guimaraes, Jose Augusto C. [UNESP] (Assoc Coll Research Libraries, 2017)
A solid professional performance on the part of academic librarians at present calls for adequate knowledge about copyright law, not only for the development of their own tasks without infringing the law, but also to guide and provide pertinent advice for library users (faculty and students). This paper presents the results of an online survey of Brazilian academic librarians, the objective being to determine the level of knowledge about basic questions on copyright related to their professional activities. The case of Brazil is especially relevant, as it is one of the few countries still not including library exceptions and limitations in its copyright law. Our results make manifest important gaps in knowledge about copyright, underlining the need for a training program to remedy the situation. Moreover, because training is needed for current as well as future professionals, it should be implemented in both the professional and the educational sector.